PENGARUH KOMPENSASI TERHADAP LOYALITAS KERJA DI HOTEL GRAND ROCKY BUKITTINGGI - Yahya, Rezima (RC-INSTITUT, 2019)
This research begins with the observation of the author at the Grand Rocky Bukittinggi Hotel and the author's observations when looking at employee loyalty at the Grand Rocky Bukittinggi which tends to fall in the past 5 months, that employees often violate regulations and often permit work. Based on the above problems this study aims to: 1) Describe employee compensation at the Grand Rocky Bukittinggi Hotel, 2) Describe the Work Loyalty of employees at the Grand Rocky Bukittinggi Hotel, and 3) Analyze the Influence between compensation and work loyalty at the Grand Rocky Bukittinggi Hotel. This type of research is classified into causal associative quantitative research with a simple linear regression test. The population in this study were all employees who worked at the Grand Rocky Bukittinggi Hotel. The research samples were 30 employees at the Grand Rocky Bukittinggi Hotel during the research period with the sampling technique being sample random sampling. Data collection techniques are carried out using a questionnaire (questionnaire) with a Likert scale that has been tested for validity and reliability. Furthermore, the data were analyzed through description analysis and simple linear regression test with the help of the SPSS Computer Program version 16.00. Based on the research that has been done, the results are as follows: 1) Compensation of Grand Rocky Bukittinggi employees shows good categories that are equal to (56.67%), 2) Work Loyalty shows no good / loyal in the category (56.67%), 3 ) The results of a simple linear regression test obtained the effect of variable employee loyalty compensation 24.5% while 75.5% was determined by other factors, F 9.109 with sig. 0,000 <0,005, then the compensation variable can explain employee work loyalty variables significantly, with an R value of 0.495. This means that compensation affects work loyalty by 49.5% and 51.5% is influenced by other factors. The significance level of 0.005 has a significant relationship between the two variables. Then obtained a regression coefficient of 0.731 with a value of sig 0,005 <0,037. This means that each increase of 1 unit of compensation will increase by 0.731 work loyalty units.